Preliminary study on characteristic of augmented reality for eco-tourism sector in Perak / Mohamad Quzami An-Nuur Ahmad Radzi ... [et al.] - Ahmad Radzi, Mohamad Quzami An-Nuur; Othman, Muhammad Fikri Saidi; Mhd Nor, Muhammad Nor Razin; Mohamad Shah, Dianna Suzieanna (2021)
This paper presents a study of augmented reality characteristics in the eco-tourism sector. Two main focuses of this study are augmented reality application and its characteristics. This study employs quantitative methods which involve collecting data from augmented reality application respondents with selected eco-tourism places. The documentation of existing augment reality, virtual reality and mixed reality become the basis of this study. Existing eco-tourism locations especially in Perak will be a significant part of this study in order to achieve its aims.